Intraoperative incision irrigation with high-volume saline reduces surgical site infection for abdominal infections - Wang, Jin; Lv, Wen; Xu, Shihai; Yang, Chao; Du, Bo; Zhong, Yuanbo; Shi, Fei; Shan, Aijun (Frontiers in Surgery, 2022)
Purpose: Surgical site infection (SSI) remains one of the most common postoperative complications for patients with abdominal infections. This study aimed at investigating the effectiveness of high-volume normal saline (NS) irrigation in preventing postoperative SSI for patients with abdominal infections. Methods: In this retrospective before-after clinical study, patients who underwent emergency laparotomy due to abdominal infections between Jan 2015 and Dec 2021 were included consecutively. A cohort of 207 patients with NS irrigation was compared to historical controls. A propensity score matching (PSM) with a 1:1 ratio was performed to reduce potential bias. The primary outcome was the 30-day SSI rate. Results: Irrigation (n = 207) and control (n = 207) matched patients were statistically identical on baseline characteristics, perioperative, and intraoperative parameters. Irrigation patients had lower overall SSI rates (10.6% vs 26.1%, P < 0.001), mainly due to reduction in superficial (4.3% vs 17.9%) and deep (1.4% vs 3.9%) SSIs, rather than space/organ SSIs (4.8% vs 4.3%). Irrigation patients also had lower rates of incision seroma (4.8% vs 11.6%, P = 0.012), shorter duration of antibiotics use (5.2 ± 1.7 d vs 7.2 ± 2.0 d, P < 0.001), and unplanned readmission (1.0% vs 8.7%, P < 0.001). Length of hospital stay showed a declining trend with irrigation intervention, while no significant difference was observed. Moreoever, logistic regression revealed that NS irrigationwas an independent protector against SSI (OR 0.309; 95% CI 0.207–0.462; P < 0.001). Conclusion: Intraoperative incision irrigation with high-volume NS is associated with a lower rate of SSI for patients with abdominal infections.